Mémoire espagnole et mémoire indienne dans un présage aztèque - Nathalie Ragot (Journal de la Société des Américanistes)
Spanish and Indian Memories in an Aztec Omen. The present article analyses an example of the problems which could occur in the process of the written memory construction. Through the comparative study of two versions of the same event, an Aztec omen about the Conquest, we’ll follow the evolution of the constituent elements of the account and their conscious and/or unconscious manipulation.